2022
DOI: 10.3390/su142113832
|View full text |Cite
|
Sign up to set email alerts
|

War Impact on Air Quality in Ukraine

Abstract: In the light of the 21st century, after two devastating world wars, humanity still has not learned to solve their conflicts through peaceful negotiations and dialogue. Armed conflicts, both international and within a single state, still cause devastation, displacement, and death all over the world. Not to mention the consequences that war has on the environment. Due to a lack of published research about war impact on modern air quality, this work studies air pollution evolution during the first months of the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…Additionally, for the territory of Ukraine it was investigated the changes in NO 2 , CO, O 3 , SO 2 , and PM 2 .5 atmospheric pollution during the first months of the full-scale war, compared to the similar periods of 2019, 2020 and 2021 [15]. The aforementioned study found a high correlation between NO 2 and PM 2 .5 with the intensity of hostilities, an increase in CO and O 3 levels, and a significant decrease in SO 2 concentrations as the war intensified.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, for the territory of Ukraine it was investigated the changes in NO 2 , CO, O 3 , SO 2 , and PM 2 .5 atmospheric pollution during the first months of the full-scale war, compared to the similar periods of 2019, 2020 and 2021 [15]. The aforementioned study found a high correlation between NO 2 and PM 2 .5 with the intensity of hostilities, an increase in CO and O 3 levels, and a significant decrease in SO 2 concentrations as the war intensified.…”
Section: Methodsmentioning
confidence: 99%
“…The psychological effects of air pollution are leading to psychiatric symptoms, including anxiety and changes in mood, cognition, and behaviour (Lundberg, 1996). It is reported by Lundberg (1996) (Zalakeviciute et al, 2022) during initial months of war, O 3 was found 2.45% higher in overall Ukraine and 3.38% higher in Kyiv; and SO 2 was 38.06% higher in overall Ukraine with 10% higher in Kyiv. There are an increasing number of studies confirming the adverse effects of air pollutants on the psychiatric disorders among citizens.…”
Section: Psychological Effects Of Air and Chemical Pollution Created ...mentioning
confidence: 97%
“…As highlighted by Zalakeviciute et al (2022), the resulting pollution has short-lived impact as well as persisting impacts. They articulate, -the toxic emissions, originating from military actions and destruction, will go on contaminating not only the atmosphere, but also water and soil, through wet and dry deposition.…”
Section: Bombing Of Industries and Chemical Pollutionmentioning
confidence: 99%
See 2 more Smart Citations